Mafia war: simulating conflict escalation in criminal organizations - Neumann, Martin (Trends in organized crime, 2017)
The paper describes a simulation model of conflict escalation in criminal organizations, investigating conditions of stability and collapse of the organization. As a paradigmatic case, the Sicilian Cosa Nostra provides the background for the formulation of the model assumptions. Cosa Nostra faced two so-called Mafia wars. Outbreak of wars is replicated by the simulation model. Since criminal organizations operate outside the state monopoly of violence, they provide a laboratory for studying war and state in the making: Organizational stability remains dependent on the loyalty of the Mafiosi. Monte-Carlo simulation experiments reveal a constant danger of a Hobbesian war of all against all. A statistical examination of explanatory factors of the distribution of violence shows that minimal differences in the initial conditions open up pathways to the escalation of violence. Central factors for stability are economic prosperity and normative commitment to the organization. Once the economic carrying capacity of the environment is reached, normative binding forces control escalation of violence. However, stability remains precarious and is in constant danger of falling in a trap cycle of revenge. This path-dependent effect is the central mechanism for the escalation of violence.